Spherical mobile robots as wireless sensor nodes for ambient temperature and relative humidity monitoring - Abad, Alexander C. (Animo Repository, 2018)
This study focuses on the design and implementation of four identical spherical mobile robots as wireless sensor nodes capable of monitoring ambient temperature and relative humidity. It uses an 11.5 cm diameter hamster-ball as its casing. Each robot is equipped with Arduino Nano, Bluetooth module, humidity and temperature sensor. An android application is used to control movements of the robots and to view the humidity and temperature reading. Bluetooth is used as the communication medium between each robot and the Android application. These robots can move forward, backward, right, left, and can form straight line and square formations. Each spherical robot uses a DC motor connected to its diameter for forward and backward movements while a servo motor is used for shifting a weight inside the ball causing it to tilt to the left or right. © 2017 IEEE.